Autoilukulttuuri modernisaation merkitsijänä suomalaissa näytelmäelokuvissa 1950- ja 1960-luvuilla - Römpötti Tommi (Finland, 2025)
The increase in private-car use is the key sign of the modernization process. In Finland, the 1950s and 1960s were a special period in the development of car culture, because the number and relative share of private cars increased and, alongside transport and drives from A to B, motoring became a way of life. In this article, I examine the ways in which car culture can be seen as a signifier of modernization in Finnish fiction films between 1950 and 1969. 1950s and 1960s saw the premiere of 334 Finnish fiction films, 223 of which feature cars. In the 1950s, almost two thirds of the films (138/210 films) contain scenes with cars, but in the 1960s, the relative number of these films is significantly higher (85/114 films). I approach the cars and car culture represented in the films in relation to the development of cars on Finnish roads, some current issues of the time, such as road accidents, cars and horses on the road, and the car-related representation of youth. From a real-life perspective, the difference in car culture between the decades is crystallized by the fact that the 1950s is the decade of import restrictions and the 1960s the decade of their end. In Finnish films of the 1950s and 1960s, the modernization of traffic is seen in the increasing number of cars, the diversification of car brands and narratively in the increasing number of shots seen from the moving car. By representing the car as a space for dialogue and placing the camera and the spectator in the moving car, the films guide the spectator to integrate into modern society. In particular, the proliferation of shots seen from the back seat of a car reflects the emphasis on individuality that characterizes modernization, in which the shared vehicle is replaced by a private one as everyday life becomes more technological.